DAMPAK PENDIDIKAN DAN PERTUMBUHAN INDUSTRI PENGOLAHAN TERHADAP PENGANGGURAN - Evi Febriani; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research is motivated by the high number of unemployed in Banten Province. In ten years, Banten Province has never been out of the top ten provinces with the highest Open Unemployment Rate in Indonesia. The situation was exacerbated when Covid-19 occurred which increased the number of unemployed. Banten province in terms of education can be said to be quite low because the RLS score is unsatisfactory, while in the industrial aspect Banten province is quite satisfactory. Based on this background, this research aims to find out the impact that education and the growth of the manufacturing industry have on unemployment. The data used are from all regencies/cities in Banten Province from 2010-2020. The method used is the panel data method using secondary data. The results of the study show that the relationship between the average length of schooling, the number of processing industries, and district/city minimum wages on simultaneous unemployment is significant. The relationship between the average length of schooling and district/city minimum wages is partially negative and significant. In the variable number of processing industries, the effect is positive. The results of the research are expected to provide an overview regarding what variables can be developed to reduce unemployment.